2020
DOI: 10.1021/acsomega.0c00160
|View full text |Cite
|
Sign up to set email alerts
|

Description of Druglike Properties of Safranal and Its Chemistry behind Low Oral Exposure

Abstract: Safranal, a plant secondary metabolite isolated from saffron, has been reported for several promising pharmacological properties toward the management of Alzheimer's disease. In the present study, we observe and report for the first time about several druglike attributes of safranal, such as adherence to Lipinski's rule of five; optimum lipophilicity; high permeability; low blood-to-plasma ratio; less to moderate propensity to interact with P-glycoprotein (P-gp) or breast cancer-resistant protein (BCRP) transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
5
13
0
Order By: Relevance
“…The concentration of rottlerin was measured by this new LC–MS/MS method, whereas standards for specific experiments were measured by our in-house HPLC–UV or LC–MS/MS methods. We performed the above-mentioned studies using our earlier reported protocols and detailed methodologies for each parameter are described in the Supporting Information.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…The concentration of rottlerin was measured by this new LC–MS/MS method, whereas standards for specific experiments were measured by our in-house HPLC–UV or LC–MS/MS methods. We performed the above-mentioned studies using our earlier reported protocols and detailed methodologies for each parameter are described in the Supporting Information.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Safranal (26) is a plant secondary metabolite isolated from saffron and was found in an aqueous infusion of P. avium leaves ( Table 3 ). Promising pharmacological properties have been described for this compound, namely neuroprotective and anti-inflammatory activities [ 40 , 41 ]. No data could be found in the literature on the presence of safranal in P. avium fruits and their by-products.…”
Section: Resultsmentioning
confidence: 99%
“…Yoshida et al observed that some monoterpenoids from Zanthoxyli fructus were inhibitors of ABCB1 protein [ 37 ] but they did not interfere with transport activity of ABCC2 and ABCBG2 [ 38 ]. Safranal was also found to affect ABCB1 and ABCG2 transporters, increasing their ATP-ase activity [ 39 ]. Potent MDR modulators have been identified among more complex terpenes such as jathropane [ 40 ] and lathyrane diterpenes [ 24 , 41 ].…”
Section: Discussionmentioning
confidence: 99%